Computed tomography perfusion imaging-guided intravenous thrombolysis in acute minor ischemic stroke - Sartor-Pfeiffer, Jennifer; Lingel, Mirjam; Stefanou, Maria-Ioanna; Krumbholz, Markus; Hennersdorf, Florian; Ernemann, Ulrike; Poli, Sven; Feil, Katharina; Ziemann, Ulf; Mengel, Annerose (Frontiers in Neurology, 2023)
Background: Over 50% of acute ischemic stroke (AIS) patients present with minor neurological deficit and optimal treatment is still debated. The randomized PRISMS trial did not show beneficial effects of intravenous thrombolysis (IVT) in unselected patients with minor stroke and non-disabling neurological deficit.Purpose: To evaluate if AIS patients with minor stroke may benefit from computed-tomography-perfusion (CTP) guided IVT. The primary endpoint was good functional outcome, defined as a modified Rankin Scale score of 0-2 at 90 days.Methods: AIS patients with NIHSS ≤5 presenting within 4.5 hours underwent multimodal CTimaging including CTP. CTP mismatch was defined as hypoperfusion on CTP with time-topeak delay >6 s without corresponding hypoperfusion in cerebral blood volume. IVT decision was left to the attending stroke physicians. Patients with large vessel occlusion (LVO) and absolute contraindications to IVT were excluded.Results: 267 consecutive patients were included (mean age: 72±14 years, 45.3% female, 75.3% received IVT, median NIHSS on admission: 3 [IQR 2, 4]). CTP mismatch was detected in 41.8% of IVT-treated patients (IVT+) and 28.8% of standard-treatment patients (IVT-) (p=0.06). IVT+ had favorable outcome at 90 days compared to IVT-(p=0.006), but no interaction with an existing CTP mismatch was detected (ORadj:1.676; 95% CI: 0.644 -4.364). No symptomatic intracranial hemorrhage according to ECASS-III criteria occurred.Although selected AIS patients with minor stroke may benefit from IVT, CTP mismatch does not correlate with functional outcome. No benefit from CTP mismatch in guiding IVT was detected in patients without LVO presenting with minor neurological deficit.